Associations of Galectin-3 Expression and LGALS-3 (rs4652) Gene Variation with Coronary Artery Disease Risk in Diabetics - Hassan, Samy; Hassaan, Mohamed; Demasy, Basma; Sabbah, Norhan (Journal of Medical Biochemistry, 2021)
Background Galectin‑3 protein that is encoded by lectin galactoside-binding soluble-3 (LGALS-3) gene serves as an important genetic factor in type 2 diabetes mellitus (T2DM) and its cardiovascular obstacles in various populations. We aimed to elicit the pro-inflammatory effect of galectin-3 as determined by interleukin-6 (IL-6) serum levels and to explore the relationship between galectin-3 (LGALS-3 rs4652) gene variation and its expression levels with coronary artery disease (CAD) risk among T2DM Egyptian patients. Methods: 112 lean subjects were compared to 100 T2DM without CAD and 84 T2DM with CAD. A tetra-primer amplification refractory mutation system polymerase chain reaction was used to test LGALS-3 (rs4652) and galectin-3 expression was tested with a quantitative real-time polymerase chain reaction. Serum IL-6 was measured using an enzyme-linked immunosorbent assay. Results: We found that the prevalence of LGALS-3 (rs4652) AC genotype and galectin-3 gene expression levels in T2DM with CAD were significantly higher than the additional 2 groups and were correlated positively to IL-6 circulating levels also, the C allele carriers (AC+CC) had significantly higher relative Galectin-3 expression levels compared to the A allele carriers (AA). Conclusion: We concluded that galectin-3 expression levels and LGALS-3 (rs4652) AC genotype were coronary artery disease risk factors in type two diabetics among an Egyptian sample.